Nihilism and the New Forms of Late-Modern Imaginary - Vercellone, Federico (Religija ir kultūra, 2013)
The article deals with the invasion of the images in our world that has produced a revolution of the aesthetic experience. Images are no longer recognised as pertaining to a universe, distinct from the real world that is apparently “suspended” in opposition to reality. They can even incorporate the medium. It is the medium that renders an image recognizable. It makes it perceivable as an image and allows us to avoid confusion with reality. This is the barrier that has been torn down, not only today, but time and again, in the history of the image, starting from Zeuxis and Parrhasius up to, with a few omissions, the phantasmagoria of the Eighteenth Century and 3D today. And it is this barrier that, from the Eighteenth Century until the present day, we have got used to defining as Nihilism. Naturally all this produces some theoretical and ethical problems. This also depends on the fact that, particularly now with digital media, we are dealing with a peculiar kind of medium, with which we enter into a relationship of exchange, it is a medium we are in. According to the author, we could define it as a “living” medium thus subverting the technique/subjectivity relationship, as it is traditionally conceived in the philosophical tradition of the Twentieth Century, so that humanity is dominated by technology and not the other way round. One more element has to be added: this is a narrative medium. It works only within the framework of an interactive relationship of exchange and dialogue with the subject that uses it. Therefore, a relationship that has great consequences develops when we come into contact with images: for example, since we are dealing with a narrative, the distinction between verbal communication and visual communication becomes fluid. This interactive relationship with the image highlights its performative virtuality and raises the ever more pressing need to develop ethics for images and new technologies. On the basis of this “living” relationship with the image, we can assert that today we are dealing with a “secular” mythology, a mythology without gods. We could say a problematic “re-enchantment of the world”.